SINGLE VERSUS MULTIPLE ARTERIAL GRAFTS: COMPARISON OF IN HOSPITAL MORTALITY - KHALID, W; IQBAL, H; AAMIR, M; INAM, T (Biological and Clinical Sciences Research Journal, 2022)
Even though not all findings have been equally positive, many retrospective studies seem to have shown an incremental survival improvement by increasing the number of arterial grafts. Multiple arterial (MultArt) grafting is only currently used in a small number of coronary arteries bypass grafting (CABG) surgeries, despite the convincing and comprehensive information in the published literature. The goal of the study is to compare the incidence of in-hospital mortality in patients following CABG with single versus multiple arterial grafts and to evaluate the frequency of single and multiple CABG arterial grafts in patients undergoing CABG for coronary arteries diseases (CAD). Following institutional review board permission, this descriptive case series was carried out at Jinnah Hospital’s heart surgery department in Lahore. 250 patients receiving CABG under general anaesthesia were a part of this study. The quantity of arteries grafted was recorded during CABG. It was observed whether there were one or several arterial grafts. A single surgical team carried out every procedure, under general anaesthesia. Patients were moved to post-surgical wards after surgery. Following surgery, patients were monitored there for 7 days. In-hospital mortality is defined as when a patient dies while receiving treatment in the hospital. In this study, inpatient mortality affected 7 (or 5.9%) of patients treated with single grafts and just 1 (or 0.8%) of patients treated with multiple grafts (p=0.022). Patients who received single graft CABG had a considerably greater incidence of in-hospital mortality. The superiority of multiple arterial graft CABG in terms of lower hospital mortality rate was demonstrated by the study’s findings.